Nontherapeutic Celiotomy Incidence is not Affected by Volume of Pancreaticoduodenectomy for Pancreatic Adenocarcinoma. Issue 8 (August 2013) - Toomey, Paul; Childs, Christopher; Luberice, Kenneth; Ross, Sharona; Rosemurgy, Alexander
Nontherapeutic celiotomy for pancreatic adenocarcinoma is detrimental to patients by delaying medical treatment as a result of unnecessarily incurred postoperative recovery time. This study was undertaken to evaluate whether surgeon volume of pancreaticoduodenectomy for pancreatic adenocarcinoma impacted the incidence of nontherapeutic celiotomy. All patients undergoing an intended pancreaticoduodenectomy for pancreatic adenocarcinoma were evaluated from 2003 to 2012. Survival was calculated using Kaplan-Meier analysis. The association between surgeon volume of pancreaticoduodenectomy and occurrence of nontherapeutic celiotomy was assessed using Fisher's exact test. Median data are presented. Eight surgeons undertook 443 intended pancreaticoduodenectomies for patients with pancreatic adenocarcinoma; 329 (74%) patients underwent pancreaticoduodenectomy, whereas 114 (26%) patients underwent nontherapeutic celiotomies. Two surgeons undertook 85 per cent of operations. Surgeon volume did not impact the incidence of nontherapeutic celiotomies ( P = 0.26). Seventy-seven (68%) patients had metastatic disease at the time of the operation, whereas 37 (32%) patients had locally advanced unresectable disease. These patients had survivals of 5.0 and 6.0 months, respectively ( P = 0.77). A high proportion of patients—one in four—undergoing pancreaticoduodenectomy for pancreatic adenocarcinoma will ultimately undergo a nontherapeutic celiotomy. Surgeon volume of pancreaticoduodenectomy for pancreatic adenocarcinoma does not lessen the incidence of non-therapeutic celiotomies. Preoperative prediction of patients with imaging-occult metastatic or locally advanced disease remains a challenge, even for high-volume surgeons. Attempts to create algorithms for patients with high risk of imaging-occult metastatic or locally advanced disease to undergo staging laparoscopy and/or positron emission tomography scanning may decrease the burden of patients undergoing nontherapeutic celiotomies.